ANALISIS TIPOLOGI ARSITEKTUR RUMAH MASYARAKAT TANI DI BANARAN KABUPATEN TUBAN - Tyas Santri (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract:. Archipelago architecture is one of the identities of the Indonesian state. Archipelago architecture in Indonesia can be found in rural areas, hamlets, villages, and coastal areas. The architecture that develops in the hamlets in Indonesia can be a potential for regional tourism development. The settlement of the peasants in Banaran Hamlet is a settlement that is not too dense and the community houses have a distinctive architectural typology. This study aims to analyze the typology of the Banaran farming community houses. This study uses a typological approach with tracing methods in the literature and field studies which are then described qualitatively. This study presents the results of the analysis of typology of farm community houses in Dusun Banaran, Sidotentrem Village, Bangilan District, Tuban Regency, East Java.Abstrak: Arsitektur nusantara merupakan salah satu identitas negara Indonesia. Arsitektur nusantara di Indonesia dapat di jumpai di wilayah pedesaan, dusun, kampung, pesisir. Arsitektur yang berkembang di wilayah dusun-dusun di Indonesia dapat menjadi potensi untuk pengembangan wisata daerah. Permukiman masyrakat tani di Dusun Banaran, merupakan permukiman yang tidak terlalu padat dan rumah msyarakat memiliki tipologi arsitektur yang khas. Kajian ini bertujuan untuk menganalisis tipologi rumah masyarakat tani Banaran. Kajian ini menggunakan pendekatan tipologi dengan metode penuelusuran secatra kajian literatur pustaka maupun lapangan yang kemudian dideskriptif secara kualitatif. Penelitian ini menyajikan hasil analisis tipologi arsitektur rumah masyarakat tani di Dusun Banaran, Desa sidotentrem, Kecamatan bangilan, Kabupaten Tuban, Jawa Timur.